Daily oral intake of theanine prevents the decline of 5-bromo-2'-deoxyuridine incorporation in hippocampal dentate gyrus with concomitant alleviation of behavioral abnormalities in adult mice with severe traumatic stress - Takeshi Takarada; Noritaka Nakamichi; Takami Kakuda; Ryota Nakazato; Hiroshi Kokubo; Shinsuke Ikeno; Saki Nakamura; Eiichi Hinoi; Yukio Yoneda (Elsevier, 2015)
Posttraumatic stress disorder is a long-lasting psychiatric disease with the consequence of hippocampal atrophy in humans exposed to severe fatal stress. We demonstrated a positive correlation between the transient decline of 5-bromo-2'-deoxyuridine (BrdU) incorporation in the hippocampal dentate gyrus (DG) and long-lasting behavioral abnormalities in mice with traumatic stress. Here, we investigated pharmacological properties of theanine on the declined BrdU incorporation and abnormal behaviors in mice with traumatic stress. Prior daily oral administration of theanine at 50-500 mg/kg for 5 days significantly prevented the decline of BrdU incorporation, while theanine significantly prevented the decline in the DG even when administered for 5 days after stress. Consecutive daily administration of theanine significantly inhibited the prolonged immobility in mice with stress in forced swimming test seen 14 days later. Although traumatic stress significantly increased spontaneous locomotor activity over 30 min even when determined 14 days later, the increased total locomotion was significantly ameliorated following the administration of theanine at 50 mg/kg for 14 days after stress. These results suggest that theanine alleviates behavioral abnormalities together with prevention of the transient decline of BrdU incorporation in the hippocampal DG in adult mice with severe traumatic stress.